1990
DOI: 10.1042/bj2670689
|View full text |Cite
|
Sign up to set email alerts
|

Translocation-independent activation of protein kinase C by platelet-activating factor, thrombin and prostacyclin. Lack of correlation with polyphosphoinositide hydrolysis in rabbit platelets

Abstract: The relationship between polyphosphoinositide hydrolysis and protein kinase C (PKC) activation was explored in rabbit platelets treated with the agonists platelet-activating factor (PAF), thrombin and 12-O-tetradecanoylphorbol 13-acetate (TPA), and with the anti-aggregant prostacyclin (PGI2). Measurement of the hydrolysis of radiolabelled inositolcontaining phospholipids relied upon the separation of the products [3H]inositol mono-, bis-and tris-phosphates by Dowex-l chromatography. PKC activity, measured in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 47 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…Within 1 min of either PAF or thrombin exposure to rabbit platelets, both the cytosolic and 1% NP40-solubilized particulate PKC activities become elevated 2-3-fold as measured in MonoQ-fractionated extracts [5,8]. Regardless of whether the Ca", diacylglycerol and phosphatidyl- Erbstatin cont.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Within 1 min of either PAF or thrombin exposure to rabbit platelets, both the cytosolic and 1% NP40-solubilized particulate PKC activities become elevated 2-3-fold as measured in MonoQ-fractionated extracts [5,8]. Regardless of whether the Ca", diacylglycerol and phosphatidyl- Erbstatin cont.…”
Section: Resultsmentioning
confidence: 98%
“…The elevation of Ca2+ and,diacylglycerol has been linked with the activation of a family of Ca2+-activated, phospholipid-dependent protein kinase (PKC) isozymes [7]. Treatment of rabbit platelets with PAF leads to 2-3-fold increases in both the activities of cytosolic and membrane-bound forms of PKC within one minute [5,8]. The pivotal role that this kinase plays in platelet activation by PAF and other cytokines is implied by the ability of a range of PKC inhibitors to block such downstream responses to these agonists as cell aggregation and the release of mediators like serotonin [9-121. Within seconds of exposure to human platelets to thrombin and collagen, enhanced tyrosine …”
Section: Introductionmentioning
confidence: 99%
“…However, there is increasing evidence showing the lack of correlation between translocation and biological effects of PKC in different cells (Bosca et al, 1989). For example, Salari et al (1990) showed that platelet activating factor, thrombin, and prostacyclin caused stimulation of both cytosolic and particulate-derived PKC in rabbit platelets. Moreover, IL-3 appeared to activate the preexisting membrane-associated PKC rather than elicit its translocation from the cytoplasm in a mast cell/megakaryocyte line R6-XE.4 (Pelech et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Since the amount of PKC as well as expression of HvPKC2 also increases in foot-regenerating fragments, and since it is unlikely that HvPKC2 should not be used for signalling there, other mechanisms must be postulated to account for PKC activation during foot formation. DAG and other PKC-activating lipids are also generated, for example, by agonist-induced hydrolysis of choline-phospholipids (Naor 1991;Nishizuka 1992), and cytosolic PKC can be activated without translocation or remain active after a short initial translocation (Salari et al 1990;Trilivas et al 1991). It remains to be clarified, if these alternative pathways are used by foot-forming tissue to activate PKC.…”
Section: Hvpkc2 and Patterning In Hydramentioning
confidence: 99%